Bionomy of coconut leaf moths (Artona catoxantha Hamps) - Sastrodihardjo, Soelaksono (Malaysian Plant Protection Society, 2013)
Bionomical information of coconut leaf moth is used to construct the population dynamic of this insect pest by means of dynamic simulation. Population samplings are carried out from three different areas, areas of frequent outbreaks (A), areas of occasional outbreaks (B) and areas of no outbreaks (C). The pattern of the population growths from these three different areas is similar except that the population peaks are the highest from A areas. At this moment it is suspected that the hyperparasitoid of Apanteles artonae, Eurytoma albotibialis Ashm, is the cause of coconut leaf moth outbreaks from the fact that the parasitization by this hyperparasitoid is the highest in the outbreaks areas